Correcting Racial Injustice: Forensic DNA Technology and the Exoneration of the Wrongfully Convicted - Rocco D'Este; Noam Yuchtman (Institute of Labor Economics (IZA), 2023)
We study the effects of laws streamlining access to post-conviction forensic DNA technology ("DNA laws"). We present a conceptual framework in which DNA laws' effects differ by race due to unequal access to non-DNA exoneration technologies. Consistent with the framework's predictions, we find that DNA laws: (i) increased DNA-based exonerations for Blacks and non-Blacks; (ii) increased total exonerations for Blacks, while non-Blacks exhibit substitution across exoneration technologies and smaller effects on total exonerations. We estimate that without DNA laws, around 100 wrongfully convicted Black Americans would have died in prison, with wrongfully convicted Blacks spending over 1,800 additional years imprisoned.
Keywords: K40; J15; D63; 330; racial inequality; criminal sentencing; legal institutions; technology and justice